Spontaneous and repeat spontaneous abortion risk in relation to occupational characteristics among working Korean women: a cross-sectional analysis of nationally representative data from Korea - Wanhyung Lee; Sung Won Jung; Young-Mee Lim; Kyung-Jae Lee; June-Hee Lee (BMC, 2019)
Abstract Background The association between spontaneous abortion (SA) and occupational characteristics among working women is not well-studied. This study aimed to assess the risk of SA and occupational factors such as occupational classification, working hours, and work schedules among working Korean women aged > 19 years. Methods In this cross-sectional study, 4078 working women were identified from among 25,534 workers in the Korea National Health and Nutrition Examination Surveys V (2010-2012) database, to obtain data on SA history and the number of SAs. Odds ratios (ORs) and 95% confidence intervals (CIs) for SA were calculated using multiple logistic regression models after adjusting for age, education, household income, cigarette smoking, alcohol consumption, and obesity status. The weighted prevalence for the number of SAs was calculated according to occupational characteristics to demonstrate the SA status among working Korean women. Results SA occurrence was reported in 5.7% of the study participants. The ORs (95% CIs) for SA were significantly higher in pink-, green-, and blue-collared workers than in white-collared workers. Regarding weekly working hours, compared with ≤50 h spent working, the ORs (95% CIs) for 51-60, 61-70, and > 70 h per week were 1.26 (0.87-1.84), 1.63 (1.04-2.56), and 1.73 (1.10-2.70), respectively. A significantly higher weighted prevalence of repeat SAs was observed in pink- and green-collared workers and in those who worked long hours. Conclusion We found a significant association between SA, repeat SA, and occupational characteristics among working Korean women.